Financial performance evaluation and bankruptcy prediction (failure) - Talal A. Al-Kassar; Jared S. Soileau (Arab Economic and Business Journal, 2014)
Despite the copious number of statistical failure prediction models described in the literature, testing of whether such methodologies work in practice is lacking. This paper examines the performance of the same companies with solvency for predicting bankruptcy and comparison in both models. This model is suggested for measuring the values of financial performance (Al-Kassar and Soileau; 2012), and applying the financial failure model (Z-score) used by Taffler (1983). The data of six companies were examined for the period 1998-2011.The methodology which used at empirical study includes measuring financial performance according to both models. Then both results have been shown in table (8). The correlations between their results for both models are shown highly relationship. They were tested by T-test. Therefore, they were classified and ranked the companies according to these values.The research also demonstrates the need to include measures of both financial and non-financial performance in the evaluation as they complement each other. Without both financial and non-financial, the evaluation process is incomplete and does not provide desired results or the correct image of the process. The research suggests including comprehensive measures of performance evaluation of projects by using indicators of adopted criteria. Thus, the application of both models leads to better results and assists users in maintaining greater objectivity while obtaining more accurate results than from analysis based on personal evaluation alone.
Keywords: 650; Financial Performance; Solvency; Bankruptcy; Criteria; Testing; Ranking